2018
DOI: 10.24099/vet.arhiv.160907
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of lameness to body condition score, udder health and milk quality in crossbred dairy cattle

Abstract: Three hundred and thirty-seven (337) crossbred dairy cows, at different stages of lactation and parity, from thirteen randomly selected dairy farms, were examined for locomotion score based on a five-point numerical scoring scale. Mild, moderate and severely lame cows were grouped together into the lame group and normal cows with locomotion score '0' into the healthy non-lame group. Body condition score (BCS) in all the animals was also evaluated on a five-point scale ranging from 1 to 5. Cows having cow hock … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 24 publications
1
8
1
Order By: Relevance
“…In lame cows, the pain associated with the severe claw lesions may decrease standing time, which in turn might result in inappropriate feeding and poor BCS in the affected cows (GOMEZ and COOK, 2010). Our results are also supported by GREEN et al (2014) andSINGH et al (2018) who showed a positive relationship between the LS and low BCS. However, other studies did not confirm improvement in body weight or BCS in dairy cows supplemented with either Zn (NOCEK et al, 2006) or biotin (MAJEE et al, 2003).…”
Section: Lactose (%)supporting
confidence: 87%
“…In lame cows, the pain associated with the severe claw lesions may decrease standing time, which in turn might result in inappropriate feeding and poor BCS in the affected cows (GOMEZ and COOK, 2010). Our results are also supported by GREEN et al (2014) andSINGH et al (2018) who showed a positive relationship between the LS and low BCS. However, other studies did not confirm improvement in body weight or BCS in dairy cows supplemented with either Zn (NOCEK et al, 2006) or biotin (MAJEE et al, 2003).…”
Section: Lactose (%)supporting
confidence: 87%
“…The general health conditions of cows in production are related to udder health. For example, it has been described that lameness in cows increases the chances of mastitis appearance and a greater SCC [ 40 ], and likewise, self-sucking, a behavior associated with stress in the lactating cow, can cause failures in teat hygiene and udder structure [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…A significant reduction in milk yield and BCS were recorded in DD-affected cows than healthy cows in our study. These findings revealed that DD and the associated lameness have negative impact on milk yield (Pavlenko et al, 2011) and BCS (Singh et al, 2018).…”
Section: Discussionmentioning
confidence: 98%